Wonders of the Invisible World: Pseudomonas syringae, the Ice Maker - Arhamar, A. S. Muhammad; Am, Septian Dwi Cahyo.; Hala, Yusminah (Universitas Sembilanbelas November Kolaka, 2025)
This literature review explores the multifaceted role of Pseudomonas syringae, a bacterium renowned for its ice-nucleating properties. Pseudomonas syringae significantly influences atmospheric processes, agriculture, and various ecosystems. These bacteria, equipped with ice nucleation proteins (INPs), facilitate ice formation at temperatures warmer than the typical freezing point, impacting weather patterns by initiating snow and hail formation. While its ice-nucleating activity can lead to frost damage in agriculture, it is also harnessed for artificial snow production. This review synthesizes findings on the bacterium's characteristics, morphology, physiology, and ecology, drawing from diverse studies. It highlights its widespread presence in various environments, including plant surfaces, water bodies, and atmospheric samples, emphasizing its adaptability and ecological significance. By employing content analysis on secondary data sources, this study provides a comprehensive understanding of Pseudomonas syringae's unique ability to mediate ice formation and its broader implications for environmental balance and biotechnological applications.Keywords: INA bacteria, Pseudomonas syringae, ice formation, InaZ protein